Optimizing Feed and Water Management in Super-Intensive Clarias gariepinus Grow-Out: A Case Study from P2MKP Raja Lele - Hardiana, Fajriyan (Aquatic Life Sciences, 2024)
This study documents the real-world implementation and outcomes of a super-intensive grow-out system for Clarias gariepinus (lele dumbo) at P2MKP Raja Lele in Banyuwangi, Indonesia. The system was conducted over a 40-day cultivation period and integrated high-density stocking, probiotic-supplemented feed, daily water quality monitoring (pH, temperature, ammonia concentration, and turbidity), and periodic size grading. Results showed a total harvest of 1,310 kg from 15,000 fingerlings with a starting biomass of 30 kg, achieving an exceptionally low feed conversion ratio (FCR) of 0.81 and a survival rate of 90.5%. Water quality parameters remained within optimal ranges, supporting healthy growth and survival. These findings indicate that when supported by disciplined management and appropriate technology, super-intensive aquaculture can significantly enhance productivity and sustainability in catfish farming.